2017
DOI: 10.1111/jnc.14021
|View full text |Cite
|
Sign up to set email alerts
|

CRIP1a inhibits endocytosis of G‐protein coupled receptors activated by endocannabinoids and glutamate by a common molecular mechanism

Abstract: The excitability of the central nervous system depends largely on the surface density of neurotransmitter receptors. The endocannabinoid receptor 1 (CB R) and the metabotropic glutamate receptor mGlu R are expressed pre-synaptically where they reduce glutamate release into the synaptic cleft. Recently, the CB R interacting protein cannabinoid receptor interacting protein 1a (CRIP1a) was identified and characterized to regulate CB R activity in neurons. However, underlying molecular mechanisms are largely unkno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 48 publications
2
30
0
1
Order By: Relevance
“…Five amino acids in the very distal carboxy terminus of CB1R are necessary for CRIP1a binding: D467, T468, S469, A472, and L473 (Mascia et al, 2017) and, interestingly, a similar motif present in the metabotropic glutamate receptor mGlu8a also binds CRIP1a (Mascia et al, 2017).…”
Section: Cannabinoid Receptor Interacting Protein 1a and 1b (Crip1a/b)mentioning
confidence: 99%
“…Five amino acids in the very distal carboxy terminus of CB1R are necessary for CRIP1a binding: D467, T468, S469, A472, and L473 (Mascia et al, 2017) and, interestingly, a similar motif present in the metabotropic glutamate receptor mGlu8a also binds CRIP1a (Mascia et al, 2017).…”
Section: Cannabinoid Receptor Interacting Protein 1a and 1b (Crip1a/b)mentioning
confidence: 99%
“…Presynaptic calcium entry is necessary for neurotransmitter release, and it is well known that CB1R activity inhibits presynaptic calcium channels. CRIP1a interacts with CB1R, suppressing the internalization of CB1R, which is essential for limiting glutamate release into the synaptic cleft [38]. The inhibition of internalization is caused by competing for β-arrestin [39,40], and it has been also reported that CRIP1a delivers newly synthesized CB1Rs to the presynaptic membrane without exogenous agonists of CB1R [41].…”
Section: Discussionmentioning
confidence: 99%
“…SGIP1, a protein linked to clathrin-mediated endocytosis, prevents internalisation of activated CB1R (Hajkova et al, 2016). Similarly, cannabinoid receptor interacting protein 1a (CRIP1a) reduces constitutive CB1R internalisation (Mascia et al, 2017) by competing with β-Arrestin binding (Blume et al, 2017).…”
Section: Discussionmentioning
confidence: 99%